Morphological Process of Lexical Morpheme in a Lover’s Complaint Poem by William Shakespeare - Rosalinda Br Nasution, Mayasari, Bima Prana Chitra (Journal of Educational Research and Humaniora (JERH), 2023)
This thesis aimed to describe the study of morphological process in the elaboration of the lexical free morpheme contained in the poem A Lover's Complaint by William Shakespeare. This research is motivated by the researcher's interest because the researcher takes this poem as the title of the thesis because it is one of the best Shakespeare love poems and its simple themes of the dangers of love so other people will be aware and understand the dangers of loving others especially women. From the morpheme that the author chose, there are 41 data for each row. 33 nouns lexical free morpheme, 18 nouns lexical bound morpheme, 19 verbs lexical free and bound morpheme, 23 adjectives lexical free morpheme, 5 adjectives lexical bound morpheme, 10 adverbs lexical free morpheme and 3 adverbs lexical bound morpheme. This research used qualitative methods and the purpose of this research was to be useful tool in implementing the researcher's knowledge of diction in a kind of lexical free morpheme in poetry.